System Analysis of a Prawn Freezing Plant - II. Maximisation of Raw Prawn Procurement and Resource Utilisation - N., Kannan; S., Bandyopadhyay (Fishery Technology, 2025)
A system analysis approach has been taken to study and analyse different alternatives of raw prawn procurement and resource utilisation of a prawn freezing unit. It has been found that linear programming models can be formulated for this type of process problems and effectively solved with the help of a computer software. Results of analysis have shown that quantities of variety-wise prawn procurement can be maximised with minimum of unutilised resource.